Review of optimal methods and algorithms for sizing energy storage systems to achieve decarbonization in microgrid applications - Hannan M.A.; Faisal M.; Jern Ker P.; Begum R.A.; Dong Z.Y.; Zhang C. (Elsevier Ltd, 2023)
Carbon; Decarbonization; Electric energy storage; Fossil fuels; Global warming; Renewable energy resources; Carbon emissions; Decarbonisation; Energy storage system; Method; Microgrid; Optimal energy; Optimization algorithms; Sizing; Storage systems; System sizings; Cost effectiveness